Implementasi Digital Marketing, Branding dan Labeling UMKM AR-ARDHO di Kota Cilegon - Framita, Dien Sefty; Maulita, Dian; Nailufaroh, Lulu; Suprihatin, Neneng Sri; Giyanti, Giyanti; Safaah, Eva; Suhartini, Suhartini (Institut Agama Islam Negeri Kerinci, 2025)
This community service aims to increase the productivity of the “AR-ARDHO” cotton candy business located in Kotabumi Village, Cilegon City, Banten through packaging innovation and the implementation of digital marketing, branding and labeling. The community service activities carried out were motivated by the problems faced by partners who have limitations in packaging and selling their products. This community service activity was carried out by providing counseling and assistance in selecting and packaging products, digital marketing systems and conducting market research related to consumer responses to new packaging. From the results of the counseling carried out, partners received a change in mindset regarding the importance of innovation in packaging and good types of packaging and a modern promotion system so that partners have the desire to change packaging and implement digital marketing in order to increase the productivity of their product sales. It is hoped that this activity will motivate partners to further innovate and learn and explore the knowledge they have regarding other marketing strategies such as promotion and distribution of the products produced.